Young people, family relationships and civic participation. Issue 1 (2nd January 2019) - Muddiman, Esther; Taylor, Christopher; Power, Sally; Moles, Kate
ABSTRACT: This article examines young people's civic participation and the extent to which this is influenced by the family. Although literature on young people's civic participation is abundant, the role of the family in influencing this participation is largely absent. Drawing on survey data collected from 976 young people aged 13–14 in South Wales, we outline the extent and nature of civic participation and how this varies according to relationships with parents and grandparents. Our data show that relationships with mothers and grandparents are particularly important in young people's accounts of their participation, suggesting that family is far more important in developing a propensity for engagement in civil society than is commonly understood.